(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The right to development is a new right that has been advocated by many international organizations, especially after the issuance of the Declaration on the Right to Development in 1986, because the development process affects all economic, human and material sectors. It is a right for all countries and peoples. However, the unilateral economic sanctions imposed on Syria, especially after the start of the war in 2011 by the United States of America and the European Union, did not take into account this right. These sanctions have led to negative results that have affected all sectors, and violate human rights in Syria, including the right to development. The living conditions of the Syrian people have deteriorated, the poverty rate has increased, the unemployment rate has increased significantly, and the GDP has decreased.